Peningkatan Hasil Belajar Siswa Menggunakan Metode Demonstrasi pada Pembelajaran PAI di SMPN 20 Bengkulu Selatan - Ummi Shaleha (Yayasan Darusssalam Bengkulu, 2025)
This Classroom Action Research (CAR) is motivated by the low learning outcomes of students in Islamic Religious Education subjects, especially the Main Material of Self-Awareness and Self-Introspection in Living Life. This is because the learning process is conventional, which is more centered on the teacher. This Classroom Action Research (CAR) aims to improve the activity and learning outcomes of students in Islamic Religious Education learning about the Material of Self-Awareness and Self-Introspection in Living Life in class VII A of SMP Negeri 20 Bengkulu Selatan through the application of the demonstration method. The benefits of this Classroom Action Research (CAR) are to provide input in renovating learning from teacher center to student center through the application of the demonstration method. Thus, students will be directly involved in seeking, finding, and exploring their own knowledge. Classroom Action Research (CAR) consisting of 3 cycles. The data in this study were obtained from teachers (observers) and students through observation, tests, and documentation. Based on the research data from cycle I to cycle III, it was obtained that the activity and learning outcomes of students in the learning process through the application of the demonstration method experienced a significant increase from previous learning using the lecture method. So, the conclusion is that the application of the demonstration method can increase the activity and learning outcomes of students in Islamic Religious Education learning about Self-Awareness and Self-Introspection in Living Life in class VII A of SMP Negeri 20 Bengkulu Selatan.